ANALISIS DAN PERANCANGAN SISTEM PENDUKUNG KEPUTUSAN PENERIMA BANTUAN PROGRAM KELUARGA HARAPAN DENGAN SIMPLE ADDITIVE WEIGHTING (SAW) PADA DINAS SOSIAL, KEPENDUDUKAN DAN PENCATATAN SIPIL PROVINSI JAMBI - Fadhliazis, Fadhliazis; Sarjono, Sarjono (Jurnal Manajemen Sistem Informasi, 2019)
There are so many programe is given by goverment to tackle proverty. One of them is Program KeluargaHarapan (PKH). But, data of beneficiery receiver is not suitable yet as something that hope. The reason is notoptimal act of determining status. Although, beneficiery receiver is not on target. Application prototypeplanner system to support final decision for PKH beneficiery receiver is used to take decision is SimpleAddictive Weighting System (SAW). It wears Use Case Diagram, Activity Diagram, and Class Diagram asmodel of system planner. Which is result assessment is done by system. That have two measurment, properor not proper. SAW Method is choosen because of this method can determine quality grade each atribute.Then, continue with rank process will do to select best alternative from a lot of alternatives. Such as; poorfamily which is include proper category based on some criterias is defineted. With that rank process,assesment will be appropriate because based on criteria grade and quality grade that determine alternative. Itwill get proper result. The result will be come holder for Social, Population, and Civil Registrationdepartment in Jambi Province. The assesment can be used to measure poor family that proper to get PKHbeneficiery. Which is this data will be given to the Ministry of Social Services of Indonesia Republic later. Itbecome proper data for goverment to give the PKH beneficiery is on the target.